Children's and adolescents' conversations with mothers about offenders' and victims' responsibility for harm in their experiences of being hurt by a peer. Issue 1 (8th June 2022) - Saint‐Martin, Anna; Badasu, Mawuena; Recchia, Holly; Wainryb, Cecilia; Dirks, Melanie
Abstract: This study investigated mothers' and children's constructions of meaning about responsibility for harm in conversations about two experiences when children were hurt by a peer and felt they had either contributed or not contributed to the situation. The sample included 105 Canadian mothers (75% White) and their children (53 girls, 52 boys) across three age groups ( M ages = 6.92, 11.14, 15.89 years). Overall, mothers and children emphasized different aspects of responsibility; mothers made more evaluations of acts and discussed the avoidability of harm whereas children referred more to hurtful acts, consequences, reasons, and subsequent responses. Discussions of the child's and peer's responsibility were responsive to the child's perspective on events. The child's responsibility for self‐protection was particularly emphasized by mothers and when the child felt they had not contributed to the situation. Children more often mitigated their responsibility as compared to their mothers, and older children referred more to their own and their peer's responsibility for harm. Findings illuminate how conversations with mothers may inform children's judgments of their own and others' roles in peer conflict.